Design and Implementation a Typical University Business Intelligence System Using Data Warehouse Technique (UBIS) - Hameed Mousa, Ayad; Talib Mohammed, Nibras; Adnan Raheem, Heba (International Journal of Engineering and Technology, 2018)
In organizations management, a Business Intelligence systems (BI) provides a flexible and computerized approach to help and support their top management (decision makers) to make better decisions. The education institutes tend to develop a Business Intelligence (BI) system to manage, integrate and control the academic information systems in terms of both data.However, until today, information does not integrate and presented in an appropriate manner for the university-decision-maker in helping them to make better decisions. The main issue is how to extract and process a massive amount of the information to speed up the intended data analysis and processing in supporting the university decision-making process. To manage and facilitate the data management process, in this paper, a university business intelligence system based on data warehouse model was designedand implemented into a case study from local education institute are carried out to explore the influences mentioned above. Finally, to find out the applicability of the proposed model the usability tested was conducted. The findings showed the applicability of the proposed system in practice.Â Â